Návrh změny organizační kultury ve vybraném podniku - Zabloudil, Aleš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato diplomová práce je zaměřena na téma orgnizační kultura a její vliv na chod regionální pobočky pojišťovny XYZ. Nejprve byly objasněny teoretické poznatky týkající se organizační kultury a jejího hodnocení. Dále byl uskutečněn polo strukturovaný rozhovor, dotazníkové šetření a provedena obsahová analýza interních dokumentů. Na základě zjištěných informací byla navržena opatření vedoucí ke zlepšení stavu z pohledu organizační kultury.

This thesis is focused on topic of organisational culture and its influence on the operation of the regional branch of the insurance company XYZ. First, the theoretical background of organisational culture and its evaluation was clarified. Furthermore, a semi-structured interview, a questionnaire survey and a content analysis of internal documents were carried out. Based on the information obtained, measures were proposed to improve the situation from the perspective of organisational culture.
Concept for Organizational Culture Change in a Company
Keywords: Organizační kultura; analýza organizační kultury; změna organizační kultury; dotazníkové šetření; Organisational culture; analysis of organisational culture; change of organisational culture; questionnaire survey